2022
DOI: 10.3390/f13060878
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Agroforestry Ecosystems: Insights into the Improvement of Service Supply Capacity of Agroforestry Ecosystems under the Karst Rocky Desertification Control

Abstract: Agroforestry provides essential ecosystem services; its structure and stability directly determine ecosystem function and service provision. Sustaining agroforestry ecosystem functions and services in the long term is necessary to meet the needs of people. This study conducted a literature search and statistical analysis based on WOS and CNKI literature databases. We reviewed 136 literature reports on studies of agroforestry ecosystem structure and stability. The landmark results are summarized in five aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 100 publications
0
17
0
1
Order By: Relevance
“…In terms of vertical structure, the three-dimensional structure of forest grassland is globally recognized as a stable state of ecosystems [ 115 , 116 ]. Studies have shown that a reasonable three-dimensional structure can effectively use light, heat, water, air and other environmental factors to improve productivity and maintain the stability of ecosystems [ 117 ], and that a composite ecosystem structure has a better soil retention effect [ 118 ]. The ecosystems of economic fruit forests and agroforestry are typical composite ecosystems, of which grassland is an essential and important component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of vertical structure, the three-dimensional structure of forest grassland is globally recognized as a stable state of ecosystems [ 115 , 116 ]. Studies have shown that a reasonable three-dimensional structure can effectively use light, heat, water, air and other environmental factors to improve productivity and maintain the stability of ecosystems [ 117 ], and that a composite ecosystem structure has a better soil retention effect [ 118 ]. The ecosystems of economic fruit forests and agroforestry are typical composite ecosystems, of which grassland is an essential and important component.…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional structure of composite ecosystems has proven to be an important strategy for reconciling environmental protection and economic development in ecologically fragile areas [ 153 ], with grasslands being the most crucial aspect, and their strong renewal rate making them a large surface area within the composite ecosystem. The resulting three-dimensional ecosystem structure not only plays an important role in maintaining and providing ecosystem services, but its multiple ecosystem services also provide an effective way to promote the restoration of degraded ecosystems, which is an important biological measure to make full use of resources [ 117 , 154 ]. A diverse three-dimensional and horizontal structure is an effective measure to restore grassland ecosystems, that is, through a combination of different species of grasses from different families (in intercropping, crop rotation, and mixed sowing, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The specific function is shown in Equation ( 3), where M is the n Ă— n direct influence matrix and a ij is the direct influence matrix that is the degree to which element i affects element j. The direct influence matrix comparison scale has five levels: no impact (0), low impact (1), medium impact (2), high impact (3), and very high impact (4), and the direct impact matrix is obtained based on the scoring judgement of experts [50].…”
Section: Index Weight Calculation Methodsmentioning
confidence: 99%
“…When the rural landscape system in KRDCA suffers from external disturbances, a good ecosystem can effectively act as a buffer to address disasters. This paper measures the quality of ecosystems from the two dimensions of ecological patterns and ecological governance [49,50]. Reasonable ecological patterns both create a good landscape effect and also effectively alleviate the impact of floods and other disasters and enhance the disaster preparedness ability of landscapes [51].…”
Section: Sociocultural Systemmentioning
confidence: 99%
“…AF has achieved excellent results in solving issues related to karst areas in recent years, especially in South China Karst, AF ecological industry models such as forest–fruit, forest–medicine and forest–grass have achieved good ecological, social and economic benefits [ 28 , 29 ]. In addition, AF development in karst areas can achieve the integrity protection of heritage sites and a mutually beneficial relationship between ecological and socioeconomic needs ( Figure 2 ), promoting sustainable region development [ 30 , 31 , 32 ] and further achieving the dual goals of development and protection [ 33 , 34 ]. At present, most studies on AF in the buffer zone of WH karst have focused on the effects of AF on hydrothermal [ 35 , 36 ], soil nutrients and biodiversity [ 37 , 38 ] and landscape and rural livelihoods [ 27 , 39 ].…”
Section: Introductionmentioning
confidence: 99%